2019
DOI: 10.1371/journal.pone.0220893
|View full text |Cite
|
Sign up to set email alerts
|

Normal Saline solutions cause endothelial dysfunction through loss of membrane integrity, ATP release, and inflammatory responses mediated by P2X7R/p38 MAPK/MK2 signaling pathways

Abstract: Resuscitation with 0.9% Normal Saline (NS), a non-buffered acidic solution, leads to increased morbidity and mortality in the critically ill. The goal of this study was to determine the molecular mechanisms of endothelial injury after exposure to NS. The hypothesis of this investigation is that exposure of endothelium to NS would lead to loss of cell membrane integrity, resulting in release of ATP, activation of the purinergic receptor (P2X7R), and subsequent activation of stress activated signaling pathways a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…This produced the maximal force tension relationship as previously described. 4 After equilibration, the rings were primed with 110 mM of potassium chloride (with equimolar replacement of sodium chloride in bicarbonate buffer) to determine functional viability. Viable rings were then tested for contractile response to a dose of phenylephrine (PE) to yield submaximal contraction (approximately 60%-70% of maximum KCl; 5 × 10 −6 M for HSV and 1-5 × 10 −7 M for RA) and relaxed with carbachol (CCH, 5 × 10 −7 M), an acetylcholine analogue, to determine endothelial-dependent relaxation responses.…”
Section: Measurement Of Endothelialdependent Relaxationmentioning
confidence: 99%
See 3 more Smart Citations
“…This produced the maximal force tension relationship as previously described. 4 After equilibration, the rings were primed with 110 mM of potassium chloride (with equimolar replacement of sodium chloride in bicarbonate buffer) to determine functional viability. Viable rings were then tested for contractile response to a dose of phenylephrine (PE) to yield submaximal contraction (approximately 60%-70% of maximum KCl; 5 × 10 −6 M for HSV and 1-5 × 10 −7 M for RA) and relaxed with carbachol (CCH, 5 × 10 −7 M), an acetylcholine analogue, to determine endothelial-dependent relaxation responses.…”
Section: Measurement Of Endothelialdependent Relaxationmentioning
confidence: 99%
“…The inner lining of the vascular wall consists of a monolayer of endothelial cells. Mechanical forces (blood flow disturbances, mechanical stretch), 1,2 chemical stressors (glycemic, oxidative, osmotic, acidosis), [3][4][5][6][7][8][9] inflammation, 10 and aging 11 are associated with dysfunction of this fragile endothelial monolayer. A common physiologic sequela of endothelial injury is impaired endothelial-dependent relaxation, often referred to as "endothelial dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“… 26 Further studies indicated that P2X7R activation promotes the neuroinflammatory response through the p38 MAPK pathway. 27 29 EA attenuates SNL-induced microglial activation mediated by p38 MAPK. 30 Therefore, we hypothesized that the analgesic effect of EA may be achieved by reducing the expression of P2X7R and thus inhibiting the phosphorylation of p38 MAPK.…”
Section: Introductionmentioning
confidence: 99%